Ethical Structures and Processes of Corporations Operating in Australia, Canada, and Sweden: A Longitudinal and Cross-Cultural Study - Svensson, Goran (Journal of business ethics, 2009)
Based on the ‘Partnership Model of Corporate Ethics’ (Wood, 2002), this study examines the ethical structures and processes that are put in place by organizations to enhance the ethical business behavior of staff. The study examines the use of these structures and processes amongst the top companies in the three countries of Australia, Canada, and Sweden over two time periods (2001–2002 and 2005–2006). Subsequently, a combined comparative and longitudinal approach is applied in the study, which we contend is a unique approach in the area of business ethics. The findings of the study indicate that corporations operating in Sweden have utilized ethical structures and processes differently than their Canadian and/or Australian counterparts, and that in each culture the way that companies fashion their approach to business ethics appears congruent with their national cultural values. There does, however, appear to be a convergence of views within the organizations of each culture, as the Swedish companies appear to have been more influenced in 2005–2006 by an Anglo-Saxon business paradigm than they have been in the past.